Explaining Regulatory Non-compliance: A Survey Study of Rule Transgression for Two Dutch Instrumental Laws, Applying the Randomized Response Method - Elffers, H. (Journal of quantitative criminology, 2003)
Within a rational choice framework, secondary data analysis of a survey study on compliance with two Dutch regulatory laws is carried out. Selection of explanatory variables to be considered is guided by a heuristic device, called the “Table-of-Eleven.” Using adapted logistic regression analysis, we show that self-reported compliance, measured by means of a randomized response procedure, can be explained in terms of benefits of non-compliance, social norms and deterrence, while knowledge and general norm-conformity have no role to play. The impact of various contributing factors turns out to be rather different in size for the two laws.